Analisis Ekspor Impor Kelapa Sawit Indonesia Dalam Meningkatkan Pertumbuhan Ekonomi - Asraaf Efendi Batubara; Muhammad Faishal Yahya; Sultan Rasy Nasyaa; Purnama Ramadani Silalahi (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
Send out is the lawful development of products, items and administrations starting with one country then onto the next, as a rule as a feature of exchange. The term